Field effect transistors on graphitized polymer surfaces - Koval, Yury; Lazareva, Irina; Müller, Paul; Müller, Klaus; Henkel, Karsten; Friedrich, Dieter (physica status solidi (b), 2011)
Conducting properties of several polymers after low-energy ion irradiation were investigated. The enhancement of conductance induced by the ions is discussed in terms of graphitization. Field effect transistors (FET) on the graphitized polymer surfaces were studied. We found that the field effect mobility depends on the conductivity of the graphitized surfaces according to the power relation σ μ. Such behavior is typical for disordered organic semiconductors with a variable range hopping mechanism of conductance. In contrast, the graphitized surfaces with a semimetallic type of conductance demonstrate a high carrier mobility 1cm/Vs, which is almost independent on the conductance. These semimetallic materials consist of 2 and 3nm graphene patches and are characterized by a significantly smaller disorder level. However, for a feasible FET application the carrier concentration in the graphitized surfaces must be reduced. Possibilities to improve the performance of the FETs are discussed. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Conductivity; Field effect transistor; Graphitization; Ion irradiation; Mobility; Polymers